Evaluation of Vitamin C Levels in Lime Fruit and Processed Passion Fruit Syrup - Lusiana Lusiana; Nur Fitria Andani; Risky Risky; Ilma Munaya; Muhammad Azman (Journal of Food Security and Agroindustry, 2026)
Vitamin C, or ascorbic acid, is a water-soluble vitamin with acidic properties and acts as a strong reducing agent. This vitamin plays an important rle as an antioxidant that protects cells and biological molecules, such as proteins, lipids, and nucleic acids, from damage caused by free radicals. This study aimed to evaluate the vitamin C content in fresh lime fruit (Citrus amblycarpa) and processed passion fruit syrup. The research employed a quantitative approach using iodometric titration analysis to determine vitamin C levels. The results showed that the vitamin C content in lime ranged from 0.179% to 0.219%, which was higher than that of passion fruit syrup, ranging from 0.032% to 0.084%. The differences in vitamin C levels were influenced by variations in raw materials, physical and chemical properties, as well as processing methods and sample testing techniques. Based on the findings, lime and passion fruit syrup have the potential to serve as sources of vitamin C, both for direct consumption and as processed products.